2020
DOI: 10.1155/2020/5846397
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Diffusion Process of Sulfate Ion in Cemented Gangue Backfill Material

Abstract: Cemented gangue backfill material (CGBM) is made of coal gangue, fly ash, cement, and water. The backfill body will be corroded by mine water that contains different kinds of corrosive ions. The paper mainly aimed to study the diffusion process of sulfate ion (SO42−) in CGBM. Soluble salt solutions with different concentrations are prepared to simulate various mine water. The SO42− concentration was measured by layered sampling method and chemical analyzing method. The diffusion coefficient was calculated acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These studies mainly focus on the experimental study of the sulfate ion transmission law, degradation of macroscopic mechanical properties, and theoretical model of sulfate attack based on mechanical and mathematical methods. Guo et al [9] tested the sulfate ion concentration in the cement gangue filling material by chemical analytical method and analyzed the degradation law via scanning electron microscopy (SEM) and X-ray diffraction (XRD). However, the transport law of sulfate ions under the influence of various environmental factors was not studied in detail.…”
Section: State Of the Artmentioning
confidence: 99%
“…These studies mainly focus on the experimental study of the sulfate ion transmission law, degradation of macroscopic mechanical properties, and theoretical model of sulfate attack based on mechanical and mathematical methods. Guo et al [9] tested the sulfate ion concentration in the cement gangue filling material by chemical analytical method and analyzed the degradation law via scanning electron microscopy (SEM) and X-ray diffraction (XRD). However, the transport law of sulfate ions under the influence of various environmental factors was not studied in detail.…”
Section: State Of the Artmentioning
confidence: 99%
“…It has demonstrated that the initial sulfate content in the interior of the CGB significantly reduces its long-term UCS, implying that one of the factors contributing to the structural deterioration of the CGB is an internal sulfate attack. Guo et al [15] studied the diffusion process of sulfate ions in cemented gangue backfill material. The results showed that the diffusion rate of sulfate ions was affected by the internal pore structure, and the changes in the internal pore structure were related to the reaction products at different times.…”
Section: Introductionmentioning
confidence: 99%
“…Gypsum is an important mineral resource and widely used in various fields [1][2][3]. At present, gypsum is mined with the room pillar method, with multiple pillars supporting the working space and isolated pillars supporting the isolated mining unit [4][5][6].…”
Section: Introductionmentioning
confidence: 99%